DONGKREK MADIUN: ANTARA SENI, TRADISI, DAN RELIGI - Alfiati Alfiati (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
In general, this study aims to obtain a clear description of the performance of Dongkrek Art in Mejayan Village, Madiun District. The focus of this research includes the ritual stage of Dongkrek Art, the meaning of the Dongkrek Art performance, and the religious values contained in Dongkrek Art. This research was conducted for 6 months, in Mejayan village of Madiun Regency. Based on the research problems that have been determined, the research design used is a qualitative research design. This study observes every ritual performed in the Dongkrek Arts performances, and searches for information from several informants or resource persons. Informants in this study is the owner of art studio dongkrek and dancer art dongkrek. Data collection techniques used in this study are interview techniques, observation techniques, and recording techniques, while data analysis techniques used are interactive analysis models.